Architecting nanographenes for efficient energy storage by tailoring molecular conformation and packing - Kumar, Viksit; Javaregowda, Bharathkumar H.; Devasia, George; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Santhosh Babu, Sukumaran (Journal of Materials Chemistry A, 2026)
Structural tuning of electrode materials to enhance electron transport, ion storage capacity, and Li+ diffusion is crucial for developing high-performance lithium-ion batteries (LIBs). In this context, organic functional materials are attractive candidates. Herein, we report a unique molecular design of regioisomeric nanographenes (NGs) with distinct geometries, packing, and topologies for lithium storage as LIB anodes. The nonplanar architectures suppress layer restacking compared to planar analogues, leading to improved electrochemical performance. The pi-extended helical NG 36NG, with larger interlayer spacing and a unique helical geometry, enables faster Li+ diffusion and delivers a higher specific capacity of 719.93 and 203.01 mAh g-1 at 0.1 and 1 A g-1, respectively, with stable performance over 6000 cycles, outperforming 27NG (525.46 and 113.17 mAh g-1 at 0.1 and 1 A g-1, respectively). Single-crystal X-ray analysis reveals markedly different molecular arrangements, directly correlating topology and packing with Li+ storage. This work highlights the critical role of molecular topology in LIB anodes and motivates the design of tailored pi-extended helical nanographenes for energy-storage applications.